2016
DOI: 10.1111/ppl.12484
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals a global insight into molecular processes regulating citrate accumulation in sweet orange (Citrus sinensis)

Abstract: Citrate, the predominant organic acid in citrus, determines the taste of these fruits. However, little is known about the synergic molecular processes regulating citrate accumulation. Using 'Dahongtiancheng' (Citrus sinensis) and 'Bingtangcheng' (C. sinensis) with significant difference in citrate, the objectives of this study were to understand the global mechanisms of high-citrate accumulation in sweet orange. 'Dahongtiancheng' and 'Bingtangcheng' exhibit significantly different patterns in citrate accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Peels were dried at 75°C for 3 days and ground immediately in a disintegrator (FW100, TAISITE, Tianjin, China). One gram powder samples were analyzed using the published method with a HITACHIL-8900 amino acid analyser (Hitachi, Wako, Japan) (Lu et al, 2016 ). To measure the targeted starch, organic acids and sugars, the isolated and frozen CK and RD peels at 40, 80, 110, 140, and 170 DAFB were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peels were dried at 75°C for 3 days and ground immediately in a disintegrator (FW100, TAISITE, Tianjin, China). One gram powder samples were analyzed using the published method with a HITACHIL-8900 amino acid analyser (Hitachi, Wako, Japan) (Lu et al, 2016 ). To measure the targeted starch, organic acids and sugars, the isolated and frozen CK and RD peels at 40, 80, 110, 140, and 170 DAFB were used.…”
Section: Methodsmentioning
confidence: 99%
“…The absolute amount of starch was determined by comparison with calibration standard curve and calculated based on peel fresh weight. Organic acid and sugar components were measured using high-performance liquid chromatography (HPLC) (LC-20A, Shimadzu, Kyoto, Japan) according to the published method (Lu et al, 2016 ). Organic acid and sugar were also determined in pulp using samples stored at −40°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete information on transcriptomes can easily be generated via high-throughput mRNA sequencing technology, which is a powerful and cost-effective tool for gene expression profiling in non-model organisms without a reference genome 10 . Illumina transcriptome de novo sequencing and assembly have been successfully used for Rutaceae plants, with recent research focusing on Citrus 11 14 and Pilocarpus species 15 . To the best of our knowledge, no studies have reported transcriptome sequencing of Zanthoxylum .…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis by high-throughput RNA sequencing (RNA-seq) is a useful tool for identifying differentially expressed genes (DEGs) under stress conditions or in tissues of different developmental stages at a genome-wide level (Lu et al 2016, Zeng et al 2016b, Ashoub et al 2018. Recently, transcriptomic analyses were conducted in rice tissues under Zn deficiency for the identification of genes associated with Zn-efficiency and Zn-deficiency responses (Bandyopadhyay et al 2017, Nanda et al 2017.…”
Section: Introductionmentioning
confidence: 99%